The Person and the City of the 20th-21st Centuries: Versions of Ukrainian and Polish Prose Fiction - Chornyi , Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose. The article examines the influence of the city on a person, component parts of the urban space that form the spirit of the city, evolution of the average city dweller and everyday life over the past hundred years, patterns of the past in modern cities. Our responses based on the analysis of the modern Poland and Ukrainian novels. Methods. The methodology of the work is based on the approaches of everyday life history and historical memory studying. We have drawn on the novels of S. Khvin, A. Stasyuk, M. Krajewski, R. Mruz, N. Osinska, J. L. Vyshnevsky, N. Gurnytska, S. Zhadan, Y. Vinnychuk, Y. Andruhovych, O. Krasovytskyi, E. Kuzhavska, M. Hrymych, published in 1995-2021. Results. Such factors as "traumatized memory", features of the creation of the city space and its markers were mainly affected the lives of residents of Gdansk, Poznan, Wroclaw, Warsaw, Lviv, Kyiv, Ivano-Frankivsk, and small cities of Donbas. The city itself erased national, estate, social, gender stereotypes and conventions. It happened faster in Poland, Ukraine is moving more slowly in this direction. Each specific city shapes its residents, and they start to feel themself like a citizens of the city and personalities. This process chiefly occurs under the influence of everyday relations between people, external political events of the national and global level, not thanks to the actions of the city authorities. Conclusions. All texts provide a holistic view on the relationship between man and the urban environment. The perception of the city by dwellers, authors and heroes of the works can be divided into several types: a magical space, a space of love, a terrain of the fight against evil, a set of stations on the route of one suburban railway line.